Developing Interactive Modules Using Learning Content Development System (LCDS) To Improve Student Learning Outcome With 4D - Mei Dian Sugiarto; Nurul Umamah; Sumardi Sumardi (JURNAL HISTORICA, 2019)
Innovations form of interactive modules using the Learning Content Development System (LCDS) can influence the existence of generation Z that is compatible with technology and has a strong desire for independent learning. Based on the results of performance analysis at SMAN 1 Purwoharjo, SMAN 1 Cluring and SMAN 1 Srono, that: (1) 80% of learning resources are used by educators and students in history learning using LKS and Package Books; (2) 50% of the media used by educators in learning in the form of PPT, videos and images so that they are less varied in learning; and (3) 75% of students are less active in learning history. Thus, to overcome this problem, researchers developed an interactive module using a Learning Content Development System (LCDS) designed to meet student needs. The purpose of this study was to develop an interactive module that was validated by experts and was able to improve the learning outcomes of X-grade secondary schools in Banyuwangi. The research method used is the 4D development model. Research data collection using observation, questionnaires, and tests. Validation results from the development of an interactive module showed that the interactive module fulfilled the validation standards of content experts by 81% with qualifications "good" , linguistic validation by 90% with qualifications "very good" , and design validation 93% with qualifications "very good", and testing of individual users 91% with qualifications "very good". Based on learning outcomes, interactive modules using the Learning Content Development System (LCDS) can be used as learning resources in schools for students. Increasing student learning outcomes with small group trials using the effectiveness test formula is 0.872% with a high category, and large group trials is 0.853% with a high category.